IOT Based Industrial Gas Leakage Detection - Muntode, Abhijeet B. Shingate; Muntode, Mayur S. Kalkhaire; KATARIA, Akash A. Shendage; KATARIA, Prof. Shende Y. N. (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Gas transmission and usage plays a very important role for cities and industries and thus in growing economies. A gas leak refers to an unintended leak of natural gas or another gaseous product. Gas leaks can be hazardous to health and the environment. Even a small leak may gradually build up an explosive or lethal concentration of gas. Gas detectors are used to detect gas such leakages. This work aims to minimize such incidents by making an IoT based gas leakage detecting device that will send a notification with the threshold value to stop further leakage for safety and maintenance. Gas sensor is connected to the Wi-Fi module where it checks the gas sensor value sent from the bolt device to the Cloud for every 10 sec and if gas concentration crosses threshold, then it switches on the BUZZER and during that time it sends an alert to your phone number. This device can be used industrially as well as commercially to monitor the concentration of the toxic gases and alert the concerned people when it crosses a certain safe limit. The device is very economical and easy to handle as the maintenance cost is low. The device is easy to use as well as simple to understand thus making it easier for large scale industrial use. In this paper we see how the existing new system is safer and economical compared to old manual gas leakage detection methods. This system generates a sound alert using buzzer on detection of a dangerous leakage and sends an SMS to the concerned person using IFTTT websites. Different colour LEDs are used to Specify the gas leaked for example, Red LED Indicates the presence of LPG. Most of the fire breakouts in industries are due to gas leaks.
Keywords: LED; IFTTT; buzzer; Gas Leak; ESP8266